Stage and cancer‐specific mortality differ within specific Asian ethnic groups for upper tract urothelial carcinoma: North American population‐based study. (3rd September 2021) - Collà Ruvolo, Claudia; Würnschimmel, Christoph; Nocera, Luigi; Wenzel, Mike; Tian, Zhe; Shariat, Shahrokh F; Saad, Fred; Verze, Paolo; Imbimbo, Ciro; Briganti, Alberto; Mirone, Vincenzo; Karakiewicz, Pierre I
Abstract : Objectives: To examine the effect of specific Asian ethnic subgroups on stage at presentation and cancer‐specific mortality in non‐metastatic upper tract urothelial carcinoma among North American upper tract urothelial carcinoma Asian patients treated with radical nephroureterectomy. Methods: We relied on the Surveillance, Epidemiology and End Results database, from 2004 to 2016. Kaplan–Meier plots and multivariable Cox regression models predicting cancer‐specific mortality were used. Results: Of 584 upper tract urothelial carcinoma patients, 173 (29.6%) were Chinese versus 130 (22.3%) Japanese versus 68 (11.6%) Korean versus 64 (11.0%) Filipino versus 40 (6.8%) Vietnamese versus 109 (18.7%) other. Vietnamese and Chinese patients showed the highest rates of T4 N0 M0 and/or T1–4 N1–2 M0 (25.0% and 18.5%, respectively), relative to other Asian ethnic subgroups. In Kaplan–Meier plots, Vietnamese patients showed the highest cancer‐specific mortality rate. In multivariable models, Vietnamese ethnicity also independently predicted higher cancer‐specific mortality (hazard ratio 2.15, P  = 0.02 and hazard ratio 1.96, P  = 0.03), relative to Japanese and Chinese patients. All other Asian ethnic subgroups showed similar cancer‐specific mortality patterns. Conclusion: Vietnamese and Chinese patients are at a stage disadvantage at upper tract urothelial carcinoma diagnosis, relative to all other Asian ethnicities. After adjustment for stage, only Vietnamese patients showed a survival disadvantage relative to all other Asian ethnic subgroups. As a result, it appears that Vietnamese patients not only present at a higher upper tract urothelial carcinoma stage, but additionally appear to harbor upper tract urothelial carcinoma that progresses at a faster rate than in other Asian ethnic subgroups.